Juvenile ossifying fibroma: Psammamatoid variant - Shivani Aggarwal; Ashish Garg; Ashim Aggarwal; Nitin Ahuja; Farzan Rehman (Wolters Kluwer Medknow Publications, 2012)
Juvenile ossifying fibroma is a rare fibro-osseous lesion containing variable amount of calcified masses, which resembles bone or cementum within a fibrocellular connective tissue stroma. It has variable clinical behavior, highly aggressive in nature including invasion and destruction of adjacent anatomic structures with a strong tendency to recur. We reported a 28-year-old female patient with a growth in the upper left vestibule region extending from canine to molar region with clinical, histopathological, and radiological features are presented. Surgical management was done, and regular follow-up was advised.